Long-term shift and recent early onset of chlorophyll-a bloom and coastal upwelling along the southern coast of Java - Horii, Takanori; Ueki, Iwao; Siswanto, Eko; Iskandar, Iskhaq (Frontiers in Climate, 2023)
Long-term change in the timing of coastal upwelling due to climate variations alters the heat budget and biogeochemical balance in the regional ocean and is an important issue in local fisheries. In this study, we investigated decadal changes in the onset of coastal upwelling along the southern coast of Java over the past two decades (2003-2020) based on the timing of chlorophyll-a (Chl-a) bloom. We estimated the bloom from satellite Chl-a concentration data. On average, the onset of coastal upwelling observed (the first Chl-a bloom of the year) was around mid-June. In the most recent decade (2011-2020), earlier-onset upwelling (before early June) was observed frequently, and the linear trend for the onset date during 2003-2020 was about 2 weeks earlier/decade. To explore the causes of the change in the timing of the upwelling, we focused on the season (April-June) during which these earlier upwelling onsets occurred, and investigated decadal changes in atmosphere and ocean conditions associated with climate change. While sea surface temperature (SST) trends reflected a basin-wide warming pattern in the Indian Ocean, warming was not significant in the southeastern Indian Ocean. During the onset period of coastal upwelling, significant SST warming trends were also observed west of Sumatra. In association with the SST warming pattern, enhanced convective activity and convergent zonal winds around Sumatra were observed. Atmospheric forcing revealed trends favoring Ekman downwelling in the equatorial eastern Indian Ocean and upwelling in the southeastern Indian Ocean, which was consistent with the trends in thermocline depth. This study provides the first results regarding the recent decadal shift in the onset timing of coastal upwelling. Ongoing monitoring is needed to better understand the long-term change of the upwelling system in the eastern tropical Indian Ocean.